A Precarious Balance Between Disaster and Miracle. Issue 1 (1st March 2022) - Extragarbo,
Abstract : We got inside making our way through debris. There were a lot of pieces of things that had been whole until recently. A lot of aluminum furniture stood side by side with large, dark, wooden armoires and frosted-glass dressers with zoomorphic paws. There were disconnected hoses, very big pots and pans, and a lot of chairs and plastic tables with folding legs. Everything was carelessly piled up at the entrance, concealing almost completely a dismal reception.